Abu Dhabi International Petroleum Exhibition and Conference 2002
DOI: 10.2118/78531-ms
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Development Approach For A Mature Oil Field

Abstract: Bahrain field, discovered in 1932, is a highly faulted asymmetrical anticline trending in North - South direction (Fig.1). There are as many as seventeen oil producing and three gas producing reservoirs within Jurassic to upper Cretaceous formations apart from the Khuff gas zones below in Permian limestone formations (Fig-2). These reservoirs occur with divergent lithology, rock and fluid properties. Some of them are saturated while some are highly under saturated. Some of them are oil wet and some water wet. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Furthermore, the fault throws and the areas of communication between Ab and the underlying zones controlled the degree of communication and the type of fluids being introduced into the Ab zones. Earlier studies has shown that Aab zone is continuously receiving fluid and pressure support in certain areas from the underlying higher pressure Mauddud zone (which is undergoing gas injection 8,9 ) through an intermediate sandstone layer, the Wara sandstone which exist in the form of erratic sand lenses distributed irregularly all over the field 6,7 .…”
Section: Production Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the fault throws and the areas of communication between Ab and the underlying zones controlled the degree of communication and the type of fluids being introduced into the Ab zones. Earlier studies has shown that Aab zone is continuously receiving fluid and pressure support in certain areas from the underlying higher pressure Mauddud zone (which is undergoing gas injection 8,9 ) through an intermediate sandstone layer, the Wara sandstone which exist in the form of erratic sand lenses distributed irregularly all over the field 6,7 .…”
Section: Production Data Analysismentioning
confidence: 99%
“…The source of water in this reservoir is lower reservoirs. And, the connectivity with lower reservoirs is provided by both fracture corridors and a high-porosity-permeability "Ac sand reservoir beneath Ahmadi 8,9 . Oil and gas production data indicated that wells in north and south have performed much better than the crestal wells.…”
Section: Production Data Analysismentioning
confidence: 99%
“…They include data acquisition/analysis campaigns for reservoir simulation to re-evaluate the remaining reserves 119,120 or revisiting/recompletion the wells 121 , re-engineering using classic reservoir engineering analysis techniques and clustering the wells based on their performances 122,123 . Another cost effective reservoir development practice was to improve the volumetric sweep efficiency through the realignment of the injection and production wells 124 .…”
Section: Reservoir Management Practicesmentioning
confidence: 99%